Pengaruh Harga dan Kualitas Pelayanan terhadap Keputusan Berkunjung Kembali melalui Kepuasan Pengunjung sebagai Variabel Intervening pada Pengunjung Ekowisata Taman Air Indonesia, Tlatar, Kabupaten Boyolali - Istikhomah, Dewi; Nugraha, Hari Susanta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2019)
Indonesian Water Park Ecotourism is a family-owned tourism business that seeks to realize the implementation of ecological management. Indonesian Water Park Ecotourism (ETASIA) is located in Tlatar Village, Boyolali Regency. This study aims to determine the effect of price and quality of service on the decision to visit again through visitor satisfaction with ETASIA visitors. The type of research used in this study is explanatory research type. Respondents in this study were 100 respondents who were ETASIA visitors. Data collection techniques were carried out using questionnaires and interviews. This study uses analysis with validity, reliability, correlation coefficient, determination coefficient, simple regression, multiple regression and t test with the help of IBM SPSS version 21.0 and sobel analysis to test the effect of intervening variables. The results showed that the price and service quality variables had a positive and significant effect on the decision to visit again through visitor satisfaction as a partially intervening variable. Suggestions that can be given to Ecotourism Water Park Indonesia is to increase visitor satisfaction through price and quality of service to be able to come up with a decision to visit again.